Institutional internationalisation through academic literacies in English: teaching and learning written genres in the Brazilian higher education context - Dutra, Deise Prina; Nunes, Leonardo Pereira; Orfanò, Bárbara Malveira; Arruda, Climene Fernandes Brito (The ESPecialist, 2019)
This contribution delves into the process of internationalisation of Brazilian higher education institutions by focusing on academic literacies in English. We highlight initiatives carried out at the Federal University of Minas Gerais in Brazil as to the teaching and learning of an array of written genres. We also assess its impact on graduate and undergraduate students’ insertion in the various international academic/scientific communities. Drawing on references within the realm of English for Academic Purposes and Academic Literacies, this work also addresses course design and application of activities concerning academic writing. Students’ personal accounts regarding their own experiences in producing written material have also been presented and discussed against the backdrop of an institutional internationalisation scenario. We concluded that the teaching and learning of written academic genres across various domains of knowledge does enhance the university’s internationalisation process both at its “at home” and “abroad” strands.